Asthma in schoolchildren in Monroe county, Florida: school-based needs assessment - Gasana, Janvier; Gibson-Young, Linda; Ibrahimou, Boubakari; Weiss-Randall, Debra; Arrieta, Alejandro; Beck-Sagué, Consuelo; Sivén, Jacqueline; Torok, Don (The Journal of asthma, 2016)
Objectives: Asthma is the most common chronic pediatric condition (14%) and the leading cause of school absenteeism in the USA. However, little is known about asthma prevalence and distribution in schoolchildren in the Florida Keys region (Monroe County). Thus, the objectives of this study were to assess asthma prevalence, symptoms, cost and distribution in schoolchildren in the Florida Keys region and to pinpoint where asthma management services are most needed. Methods: Cross-sectional survey data on asthma prevalence, symptoms and socio-demographics was collected and analyzed by race, sex, grade and zip code. A total of 2313 parents of schoolchildren in the Florida Keys completed the adapted Harlem Empowerment Zone Asthma Initiative Questionnaire. The questionnaire was distributed to school principals, who sent them home with students to be filled out by parents or caregivers. We also analyzed data from the online Monroe County 2012 Florida Youth Tobacco Survey, the 2011 Florida CHARTS, the Medical Expenditures Panel Survey, and emergency departments (ED). Data were analyzed by race, sex, and grade. Results: In total 14.5% of respondents had been told their child had asthma and 9.6% reported their child had wheezing in the last 12 months. The prevalence was higher in the Lower Keys and Key West regions. Parents from households where anyone smoked cigarettes (OR 1.52, 95% CI 1.11-2.09) and those who had a male child (1.53, 1.17-2.00) more often reported that their child had asthma. The rate of asthma-related ED visits for Black non-Hispanic schoolchildren (1202 per 100 000) was substantially higher than the numbers for White (250.2 per 100 000) and Hispanic schoolchildren (325.1 per 100 000). Most of the direct cost of asthma was concentrated in children in grades four through seven ($1236.02-$2147.02 per child). Conclusions: The asthma prevalence in a sample of schoolchildren in the Florida Keys region was comparable to the nationwide prevalence. Black non-Hispanic schoolchildren had more asthma-related ED visits that White and Hispanic schoolchildren. Most of the direct cost of asthma is concentrated in children in late elementary through early middle school grades. Interventions are needed, particularly targeting Black schoolchildren in late elementary through early middle school grades in Lower Keys and Key West region.